Evaluating Virtual Patient Interaction Fidelity With Advanced Communication Skills Learners - Carnell, Stephanie; Miles, Anna; Lok, Benjamin (Frontiers in Virtual Reality, 2022)
Previous research in educational medical simulation has drawn attention to the interplay between a simulation’s fidelity and its educational effectiveness. As virtual patients (VPs) are increasingly used in medical simulations for education purposes, a focus on the relationship between virtual patients' fidelity and educational effectiveness should also be investigated. In this paper, we contribute to this investigation by evaluating the use of a virtual patient selection interface (in which learners interact with a virtual patient via a set of pre-defined choices) with advanced medical communication skills learners. To this end, we integrated virtual patient interviews into a graduate-level course for speech-language therapists over the course of two years. In the first cohort, students interacted with three VPs using only a chat interface. In the second cohort, students used both a chat interface and a selection interface to interact with the VPs. Our results suggest that these advanced learners view the selection interfaces as more appropriate for novice learners and that their communication behavior was not significantly affected by using the selection interface. Based on these results, we suggest that selection interfaces may be more appropriate for novice communication skills learners, but for applications in which selection interfaces are to be used with advanced learners, additional design research may be needed to best target these interfaces to advanced learners.